Cancer in primary immunodeficiency diseases: Cancer incidence in the United States Immune Deficiency Network Registry - Mayor, Paul C.; Eng, Kevin H.; Singel, Kelly L.; Abrams, Scott I.; Odunsi, Kunle; Moysich, Kirsten B.; Fuleihan, Ramsay; Garabedian, Elizabeth; Lugar, Patricia; Ochs, Hans D.; Bonilla, Francisco A.; Buckley, Rebecca H.; et al. (Journal of allergy and clinical immunology, 2018)
We evaluated the overall and site-specific incidence of cancer in subjects with primary immunodeficiency diseases (PIDD) enrolled in the United States Immune Deficiency Network (USIDNET) registry compared with age-adjusted cancer incidence in the Surveillance, Epidemiology and End Results Program (SEER) database. We hypothesized that subjects with PIDD would have an increased incidence of cancer due to impaired immune function. Overall and site-specific cancer incidence rates were evaluated in subjects with PIDD (n = 3658) enrolled in the USIDNET registry from 2003 to 2015 and compared with age-adjusted incidence rates in the SEER database. We observed a 1.42-fold excess relative risk of cancer in subjects with PIDD compared with the age-adjusted SEER population (P < .001). Men with PIDD had a 1.91-fold excess relative risk of cancer compared with the age-adjusted male population (P < .001), while women with PIDD had similar overall cancer rates compared with the age-adjusted female population. Of the 4 most common malignancies in men and women in SEER (lung, colon, breast, and prostate cancers), we found no significant increase in these diagnoses in subjects with PIDD. Significant increases in lymphoma in both men (10-fold increase, P < .001) and women (8.34-fold increase, P < .001) with PIDD were observed. Excess incidence of cancer occurred in subjects with PIDD. An excess of lymphoma in specific PIDD populations principally drove this increased incidence, while no increased risk of the most common solid tumor malignancies was observed. These data point to a restricted role of the immune system in protecting from specific cancers.